COLLABORATIVE PARTNERSHIP IN HANDLING OF STREET CHILDREN'S PROBLEMS IN SETIAMANAH DISTRICT CENTRAL CIMAHI SUBDISTRICT CIMAHI CITY - Mari Esterilita; Ellya Susilowati; Krisna Dewi Setianingsih (Politeknik Kesejahteraan Sosial Bandung, 2018)
Handling the problem of street children in Kelurahan Setiamanah has not optimally synergized with the stakeholders in handling child problem. This study aims to photograph and develop collaborative partnerships in handling the problem of street children in Kelurahan Setiamanah, Kecamatan Cimahi Tengah, Kota Cimahi with research questions, namely how the initial conditions, how the development needs, how the development design, how the implementation and development design results, and how the improvement of design development partnership collaborative. this study focuses on aspects of network structure, commitment, trust, sharing of information, sharing of accountability / responsibility and access to resources. The research method used is qualitative method with action research design. Participants in the research are community, parents and street children, and organizational board. Data collection techniques are Focus Group Discussion, interview, observation and documentation study. The result of the research shows that the use of collaborative partnership can synergize the handling of street children in Setiamanah Village with the formation of network structure with Leading sector comes from local community, Commitment made Written through agreement pledge and agreed in Forum, Accountability sharing is done according to role and capacity of stakeholders, information sharing (Formal Meeting, Infrared Meeting, whatsapp Group. Access resources (capacity building of human resources).